2019
DOI: 10.3390/app9051032
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carbon Nanotubes on Chloride Penetration in Cement Mortars

Abstract: The study investigates the effect of carbon nanotubes on chloride penetration in nano-modified mortars and reports on the physical, electrical, and mechanical performance of the material. Mortars were artificially corroded and their surface electrical surface conductivity as well as flexural and compressive strength were measured. The influence of variable nanotube concentration in accelerated corrosion damage was evaluated. Nanotube concentration was found to significantly affect the permeability of the morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 50 publications
(77 reference statements)
1
12
0
2
Order By: Relevance
“…La Ref. [46], realiza el estudio de la penetración al oxígeno del concreto a la edad de 28 días de dos mezclas de concreto con NTC y una mezcla de concreto convencional (0%), empleando las cantidades de 0.2% y 0.5% NTC. Los resultados revelan que la profundidad al oxígeno decrece con el incremento de la adición de NTC, obteniendo los valores de 5.1 cm y 2.5 cm para las mezclas de 0.2% de NTC y 0.5% NTC, comparados con la profundidad al oxígeno de 8.8 cm para 0% que equivale a los porcentajes de disminución del 42 % y 71%.…”
Section: Permeabilidad Al Aguaunclassified
See 1 more Smart Citation
“…La Ref. [46], realiza el estudio de la penetración al oxígeno del concreto a la edad de 28 días de dos mezclas de concreto con NTC y una mezcla de concreto convencional (0%), empleando las cantidades de 0.2% y 0.5% NTC. Los resultados revelan que la profundidad al oxígeno decrece con el incremento de la adición de NTC, obteniendo los valores de 5.1 cm y 2.5 cm para las mezclas de 0.2% de NTC y 0.5% NTC, comparados con la profundidad al oxígeno de 8.8 cm para 0% que equivale a los porcentajes de disminución del 42 % y 71%.…”
Section: Permeabilidad Al Aguaunclassified
“…Los resultados mostrados muestran la misma tendencia de disminución de la penetración al oxígeno y del coeficiente de permeabilidad al agua que los estudiados, donde su comportamiento se debe a que las nano partículas al dispersarse uniformemente en la matriz de cemento la hacen más homogénea y compacta con lo cual reducen el paso del agua a través del concreto [46].…”
Section: Permeabilidad Al Aguaunclassified
“…The incorporation of nanomaterials including MWCNTs in building materials is increasingly being characterized in order to enhance the mechanical, physical, and electrical properties of the structures, while reducing their failure. Dalla et al [14] studied the influence of introducing MWCNTs as nano-reinforcements in cement mortars. The obtained results showed that the permeability, electrical resistivity, and the flexural and compressive properties of the mortars were significantly affected by the inclusion of MWCNTs at levels ranging from 0.2-0.8 wt % of cement [14].…”
Section: Cementitious Materialsmentioning
confidence: 99%
“…Dalla et al [14] studied the influence of introducing MWCNTs as nano-reinforcements in cement mortars. The obtained results showed that the permeability, electrical resistivity, and the flexural and compressive properties of the mortars were significantly affected by the inclusion of MWCNTs at levels ranging from 0.2-0.8 wt % of cement [14].…”
Section: Cementitious Materialsmentioning
confidence: 99%
“…Most research on CNT addition has been conducted to reveal the mechanical properties as well as the microstructures of CNT-cement composites [13][14][15][16]. In addition, several studies have been conducted on the durability of CNT-cement mortars [17,18].…”
Section: Introductionmentioning
confidence: 99%